Mixed heterotopic gastrointestinal cyst and extranasal glial tissue of oral cavity with cleft palate - Teerthanath Srinivas; Kailkere Padma Shetty; Hariprasad Sinivas (Wolters Kluwer Medknow Publications, 2011)
Mixed choristomas of the oral cavity are uncommon lesions that show a variety of clinical presentations, histological appearance and growth patterns. Mixed choristoma with cleft palate is a very rare developmental malformation. We report an unusual case of mixed choristoma in posterior tongue and left submandibular region in a 6-month-old male baby who had cleft palate. The patient presented with spontaneous bleeding from mouth and recurrent swelling in submandibular region. The histology of the surgical resected specimens displayed features of heterotopic oral gastrointestinal cyst and glial choristoma. The swelling recurred 1 year after surgery; the histology of the second surgical resected specimen displayed scattered islands glial tissue.